2016
DOI: 10.1097/nur.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Nurse Specialist–Led Interprofessional Quality Improvement Project to Reduce Hospital-Acquired Pressure Ulcers

Abstract: This quality improvement project is a successful example of an interprofessional clinical nurse specialist-led initiative that impacts patient/family and organization outcomes through the identification and implementation of evidence-based nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…By consulting a biostatistician at the onset of the study, we employed rigorous statistical measures to determine appropriate sample size and significance of outcomes of an evidence-based PUPP. Congruent with results of previous quality improvement and research projects (Baldelli & Paciella, 2008;Chaboyer et al, 2015;Fabbruzzo-Cota et al, 2016;Hunter et al, 2014;Murray, 2012;Tayyib & Coyer, 2017), implementing an evidence-based PUPP resulted in reductions of PU prevalence and incidence. The majority of previous studies reported these reductions as percentages.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…By consulting a biostatistician at the onset of the study, we employed rigorous statistical measures to determine appropriate sample size and significance of outcomes of an evidence-based PUPP. Congruent with results of previous quality improvement and research projects (Baldelli & Paciella, 2008;Chaboyer et al, 2015;Fabbruzzo-Cota et al, 2016;Hunter et al, 2014;Murray, 2012;Tayyib & Coyer, 2017), implementing an evidence-based PUPP resulted in reductions of PU prevalence and incidence. The majority of previous studies reported these reductions as percentages.…”
Section: Discussionmentioning
confidence: 95%
“…This study's results are discussed within the context of current evidence. The literature was reviewed for Canadian studies and one report by Fabbruzzo-Cota et al (2016) was located. A clinical nurse specialist-led quality improvement project was described and it reduced hospital-acquired PUs in a tertiary care hospital in Toronto, Canada (Fabbruzzo-Cota et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an environment of disinvestment in nutrition and dietetic services (Bell et al, ), it is critical for all members of the health‐care team to work together to prioritize mealtimes. A more coordinated and collaborative approach at mealtimes could be promoted by establishing forums to discuss the delivery of nutrition care; dedicated, interprofessional, collectively‐competent mealtime teams; and nutrition champions to enact positive mealtime strategies (Fabbruzzo‐Cota et al, ; Tappenden et al, ). We have shown that engagement of volunteers and visitors could also support positive mealtime experiences and staff work practices (Ottrey, Palermo, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a multimethods, randomized cluster study done in the United Kingdom, it was found that the multidisciplinary teams designated for wound care in long‐term care facilities had a cost reduction and efficacy that was driven by the role of the APRN (Stern et al., ). An 80% reduction in HAPIs was noted when the role of the clinical nurse specialist (CNS, one type of APRN) was utilized to implement a strategic pressure injury prevention program in a hospital setting (Fabbruzzo‐Cota et al., ).…”
Section: Introductionmentioning
confidence: 99%